2012
DOI: 10.1016/j.jpain.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Persistent Postsurgical Pain in Women Undergoing Hysterectomy Due to Benign Causes: A Prospective Predictive Study

Abstract: Persistent postsurgical pain (PPSP) is a major clinical problem with significant individual, social, and healthcare costs. The aim of this study was to examine the role of demographic, clinical, and psychological risk factors in the development of PPSP after hysterectomy due to benign disorders. In a prospective study, a consecutive sample of 186 women was assessed 24 hours before surgery (T1), 48 hours after surgery (T2), and 4 months after surgery (T3). Regression analyses were performed to identify predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
7
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 86 publications
8
97
7
2
Order By: Relevance
“…For instance, it has been shown that factors like presurgical anxiety, expected pain, and pain catastrophizing have predictive value for postoperative pain after otorhinolaryngologic or other kind of surgery. 14,15 The undersupply with adequate pain management after surgery is not a specific problem of otorhinolaryngologic surgery. It seems to be a general problem after any kind of surgery.…”
Section: Minimal Painmentioning
confidence: 99%
“…For instance, it has been shown that factors like presurgical anxiety, expected pain, and pain catastrophizing have predictive value for postoperative pain after otorhinolaryngologic or other kind of surgery. 14,15 The undersupply with adequate pain management after surgery is not a specific problem of otorhinolaryngologic surgery. It seems to be a general problem after any kind of surgery.…”
Section: Minimal Painmentioning
confidence: 99%
“…38 A study of 56 patients undergoing thoracotomy found that 54% of patients reported chronic pain at a median of 25.5 months after surgery. 39 Of the 30 patients reporting chronic pain, pain was described as "constant" for 33%, "on and off" for 17%, "a few times per week" for 37%, and "a few times per month" for 13%.…”
Section: Delineating Short-term Versus Longer-term Variations In Postmentioning
confidence: 99%
“…[5] Several factors, including intensities of preoperative and postoperative pain, the approach and type of surgery, and genetic factors, contribute to the risk of pain chronicity. [6] Nevertheless, limited information is available about pain chronicity after gynecological operations.…”
Section: Introductionmentioning
confidence: 99%